Corporate investment, government control, and financing channels: Evidence from China's Listed Companies - Firth, Michael; Malatesta, Paul H.; Xin, Qingquan; Xu, Liping (Journal of Corporate Finance, 2012)
We investigate the relation between the internally generated cash flows and fixed asset investments of Chinese firms and find that it is U-shaped. Cash flow and investment are negatively related for low levels of cash flow but positively related for high levels of cash flow. We find that government controlled listed firms have greater investment–cash flow sensitivities than do privately controlled listed companies, especially on the left-hand side of the U-shaped curve where cash flow is negative. However, the difference in sensitivities appears only among firms that possess few profitable investment opportunities. We attribute this finding to the government having multiple socio-economic objectives, which leads to increased capital expenditures by the firms it controls when internal funds are abundant and when internal funds are negative. There is no evidence that access to finance and soft budget constraints explain the differences between the investment–cash flow sensitivities of government controlled and privately controlled listed firms.